If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-11=5x-7
We move all terms to the left:
6x-11-(5x-7)=0
We get rid of parentheses
6x-5x+7-11=0
We add all the numbers together, and all the variables
x-4=0
We move all terms containing x to the left, all other terms to the right
x=4
| -13.9=-1.1+x/8 | | 12n-9n-6+10=0 | | (2x+6)^2=2x-6 | | 7=4v+3 | | 5+7×=45+3x | | |x-2|-1=5 | | 6-x=3x+17 | | 2x^2=2(11x-48) | | -2x^2=2(11x-48) | | 7(x-5)=5(x-8) | | -14+60+7-2b=1+5b | | 4/104=x/468 | | 2n/3+n=1-0,6 | | 8x+8548x²=20 | | 4t-9t+t-2t=5-11 | | 6x+14=2x+5 | | y+7y=-8+7 | | Y-6y+9y=0 | | 2+.20x=5+.20x | | -12+24=-3x+8 | | -5n-9=-46 | | 2x3+x2−7x−6=0 | | 7+.20x=5+.20x | | 6=40-y | | 5x2+6x−2=0 | | y/4+ 19= 25 | | y4+ 19= 25 | | 76=12+8m | | 6(x+7)+9=6x+5 | | 4x+2x(x-1)=-20 | | 4x^2-13=12 | | 5*0.4+x*0.6=4 |